Pocket guide to the operating room - Goldman, Maxine A. (Philadelphia, Pennsylvania : F. A. Davis Company, 1996)
This guide is intended for the practitioner, as well as the student surgical technologist or nurse who requires a concise, yet comprehensive reference regarding the technological aspects of the care of the patient in the operating room.
Part 1 Perioperative considerations -- Part II Anesthesia -- Part III Surgical procedures including procedures -- Part IV Instrument trays.
Includes bibliographical references and index.
Keywords: SURGERY, OPERATIVE --HANDBOOKS, MANUALS, ETC